123k views
5 votes
(-5) (16) (-3) (-2) =

User Mitchus
by
5.8k points

1 Answer

4 votes

Final answer:

The expression (-5) (16) (-3) (-2) can be simplified by multiplying the numbers together. The product is 480.

Step-by-step explanation:

The expression (-5) (16) (-3) (-2) can be simplified by multiplying the numbers together. When two negative numbers multiply, the product is positive. So, we have:

(-5) (16) (-3) (-2) = (-5) x (16) x (-3) x (-2) = 80 x 6 = 480

Therefore, the answer is 480.

User Sourabh Choure
by
5.9k points